Combustion-induced turbulent flow fields in premixed flames. (15th April 2021) - Bradley, D.; Lawes, M.; Morsy, M.E.
Abstract: Combustion-induced turbulence is studied in explosions of methane/air in a steel sphere with optical access. Rms turbulent velocities, u ', created by four peripheral variable speed fans, were measured by Particle Image Velocimetry, PIV, which indicated near-uniform, isotropic turbulence, with small mean velocities. The gaseous expansion of a near-spherical propagating flame generated a radially outwards velocity of unburned mixture, the intensity of which depended upon the burning velocity and volume increase due to combustion. The study is to measure any extra turbulence created by this outwards velocity pulse. Only wave lengths less than the flame circumference can wrinkle the flame and increase the burning velocity, u t . Consequently the effective rms velocity at the flame front affecting its propagation, u k ', is less than u ' . Analysis shows, u k ', to be a function of flame radius. The velocity pulse generated additional turbulence, enhancing u k ' . This enhanced u t, giving further positive feedback. This higher rms value is designated as a spatial rms turbulent velocity, u s ' . PIV-measured gas velocities are resolved into a mean radial velocity, U - r and, u s ', with their radial profiles. These are derived from explosions at different equivalence ratios, pressures, and temperatures. At the radii at which u t are measured, u s ' / u k ' is enhanced by the high rates of burning and volumetric expansion. This ratio attained a high value of 2.5, with stoichiometric CH4 /air. Values of u t measured in explosions are higher than those measured in steady-state burners, attributable to the induced u s ', enhancing u t, in explosions, with no such effect in burners.